Pengaruh Disiplin Terhadap Prestasi Belajar Siswa Kelas X IPS Di SMA Negeri Weluli Kabupaten Belu: Indonesia - Lopo, Ferdinan Leonadus; Olok, Wilhelmina (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The purpose of this study was to determine the effect of discipline in attending lessons and discipline in doing assignments together on the learning achievement of Class X IPS students at SMA Negeri Weluli, Belu Regency. This study used a quantitative approach with a sample of 29 students and showed partial test results (t test), obtained that the tcount value of each independent variable (X1 = 5.201, X2 = 21.87) is greater than the ttable value (2.045). This explains that the discipline variables (taking lessons and doing assignments) partially (each) affect the learning achievement of Class X IPS students at SMA Negeri Weluli, Belu Regency. Simultaneous test results (F test), explains that Fcount (13.778) is greater than Ftable (3.37). This shows that the discipline variable (taking lessons and doing assignments) simultaneously (together) influences the learning achievement of Class X IPS students at Weluli Public High School, Belu Regency.